THE STRUCTURE OF BIRDS, AN OVERVIEW OF SEVERAL EXAMPLE - NILAM KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
The structure of birds is a remarkable example of adaptation and evolution, with a wide range of structural adaptations that enable them to fly, survive, and thrive in various environments. This paper provides an overview of several examples of bird structure, including the wings and feathers of penguins and owls, the beaks of woodpeckers and pelicans, and the feet of hawks and eagles. The paper also highlights the importance of bird structure in their behavior, ecology, and interactions with other organisms, as well as its practical applications in areas such as technology development and conservation.